Improvement of Panel Assembly Competence through Learning Using FluidSIM Simulation Software Integrated with Student Video-Based Presentations - Siswandi Siswandi; Yoto Yoto; Widiyanti Widiyanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
The rapid advancement of information and communication technology has changed learning strategies in vocational education, particularly in engineering, which requires mastery of practical competencies. This study aims to evaluate the effectiveness of learning using FluidSIM simulation software integrated with student video-based presentations in improving learning outcomes in the Panel Motor Assembly subject at SMKN 1 Blitar. This study used a quantitative experimental design with two groups: the experimental group that received learning assisted by FluidSIM software simulation and video-based presentations, and the control group that used conventional instruction. Data were collected through practical tests, observation, and questionnaires, and then analyzed using descriptive and inferential statistics. The results of the study showed that the experimental group achieved a higher average score (87.5) than the control group (70), indicating improved students’ conceptual understanding and technical skills. The integration of video-based presentations and simulations also promotes problem-solving skills, reflective learning, and communication. Therefore, it can be concluded that technology-based learning, by integrating FluidSIM simulation software with students video-based presentations, is effective in improving vocational students' performance and supporting the development of 21st-century competencies